2008
DOI: 10.1007/bf03175545
|View full text |Cite
|
Sign up to set email alerts
|

Freezing effects on survival ofListeria monocytogenes in artificially contaminated cold fresh-salmon

Abstract: The effects of freezing at -20 °C were examined on surviving of Listeria monocytogenes contaminating food during freezing. Slices of fresh salmon were inoculated with three strains of Listeria monocytogenes (10 8 CFU/g). The inoculated pieces of fish were dried for 1 h at 24 °C and then stored in closed containers at -20 °C for ten months. The identification of atypical cells found after freezing was achieved by PCR. This technique was based on the amplification of two specific genes of L. monocytogenes hlyA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 26 publications
(28 reference statements)
2
31
0
2
Order By: Relevance
“…Other freezing-related changes in microstructure of fish muscles, such as increase in extracellular space and shrunken muscle fibers, leads to an increased surface area, which provides for more physical space and better access to nutrients (44). Several studies have been conducted to determine the effect of freezing stress on growth of L. monocytogenes on various food products including cold-smoked salmon; fresh salmon; chilled, cooked shrimp; and frankfurters (5,27,31,53). However, the information regarding the impact of process ing and postprocessing handling of food products on growth of L. monocytogenes is limited.…”
Section: Figure 1 Cell Density Of Listeria Monocytogenes Strains Ovementioning
confidence: 99%
See 1 more Smart Citation
“…Other freezing-related changes in microstructure of fish muscles, such as increase in extracellular space and shrunken muscle fibers, leads to an increased surface area, which provides for more physical space and better access to nutrients (44). Several studies have been conducted to determine the effect of freezing stress on growth of L. monocytogenes on various food products including cold-smoked salmon; fresh salmon; chilled, cooked shrimp; and frankfurters (5,27,31,53). However, the information regarding the impact of process ing and postprocessing handling of food products on growth of L. monocytogenes is limited.…”
Section: Figure 1 Cell Density Of Listeria Monocytogenes Strains Ovementioning
confidence: 99%
“…Among the processing procedures, salting, smoking, and freezing are known to influence the survival and growth of L. monocytogenes (49) on cold-smoked salmon. The effect of freezing stress on the growth of L. monocytogenes has been assessed in cold-smoked salmon; in all cases, L. monocy togenes was inoculated onto cold-smoked salmon prior to freezing (5,27,31,53). Aside from the effect of freezing on L. monocytogenes, freezing salmon before or after smoking causes structural and chemical changes (39,44).…”
mentioning
confidence: 99%
“…A similar study reported that levels of L. monocytogenes were reduced by less than 1-log in frozen fish and shrimp during three months of storage at −20 °C [29]. Another study investigating survival of L. monocytogenes reported a 3.69-log reduction in frozen salmon inoculated with a high level (10 8 CFU/g) and stored at −20 °C for 12 months [30]. These results indicate that frozen products may carry L. monocytogenes even after months of frozen storage if the products were contaminated with L. monocytogenes .…”
Section: Resultsmentioning
confidence: 99%
“…Listeria monocytogenes has been recognized as a human pathogen since 1929 (Jay 2000). Because of its specific population's targets, such as pregnant women and immunocompromised patients, it is classified as an opportunistic pathogen (Miladi et al . 2008).…”
Section: Introductionmentioning
confidence: 99%